Pertanggungjawaban Pidana Korporasi dalam Korupsi Pengadaan Barang dan Jasa Konstruksi - Galuh Nur Hasanah; Anita Zulfiani (Universitas Sang Bumi Ruwa Jurai, 2023)
The development of criminal law is now beginning to recognize corporations as entities subject to criminal law, so that corporations suspected of committing criminal acts can also be held criminally responsible. This study aims to analyze the concept of criminal liability for corporations that commit corruption in the field of procurement of goods and construction services. The method used in this paper uses normative juridical law research by conducting a study of literature materials in the field of law related to the research topic. This research uses a statute approach and a case study. The results showed that in looking at criminal liability for corporations suspected of committing criminal acts, they must first see and know a mistake from the corporation. The imposition of penalties and determination of the amount of substitute money to be paid to corporations proven to have committed corruption should require new arrangements because existing legal regulations currently have limitations in certain cases prohibited from containing more arrangements than the provisions contained by law.